Concepts of Indian Traditional Aesthetics and Fine Arts as Gleaned From Major Śaivāgamic Texts in Hindu Religion - Balakailasanathasarma, M. (The Royal Asiatic Society of SriLanka, 2016)
Historically, Indians have applied aesthetic principles even in religious rituals. The Indus valley people worshiped their deities with music and dance. Vedic fire altars were constructed according to aesthetic norms. Śaivagamic texts are also to be accepted to contain the earliest art - tradition in India so far as the arts of architecture and sculpture are concerned. The aim of this study is to identify the elements and influence of religious and ritualistic aspects of Śaivagamic texts in Indian traditional aesthetics and Fine Arts.
Keywords: Śaivagamic Texts; Aesthetics; Fine Arts; Rituals